A Transpersonal Festschrift to Honor Charles Tart on his 85th Birthday - Cunningham, Paul (Journal of Anomalous Experience and Cognition, 2023)
This summary honors Charles Tart on his 85th birthday by reviewing his contributions and the influence of his work in the subdiscipline of Transpersonal Psychology. Six contributions are reviewed, namely his vision of Transpersonal Psychology as: (a) a science of Mind and Spirit, (b) a critical psychology, (c) an empirical, non-churchly approach to religion as spiritual psychology, (d) a state-specific science of exceptional human experience, (e) an evidence-enriched science of spirituality grounded in the scientific foundations of experimental parapsychology, and (f) a psychology of human possibilities to help individuals overcome obstacles to growth.